One step synthesis of chromium-containing periodic mesoporous organosilicas and their catalytic activity in the oxidation of cyclohexane - Shylesh, S.; Srilakshmi, Ch.; Singh, A. P.; Anderson, B. G. (Microporous and Mesoporous Materials, 2007)
Chromium-containing ethane-bridged hybrid mesoporous materials (Cr-PMO) with uniform hexagonal arrangement were synthesized by two different synthesis routes using 1,2-bis(triethoxysilyl)ethane (BTEE) and tetraethyl orthosilicate (TEOS) as silica sources and alkyltrimethyl ammonium salts (ATMA) as surfactants. Powder X-ray diffraction, TEM, N-2 adsorption-desorption, FT-IR, in situ FT-Raman, UV-ViS, XPS, Si-29 MAS NMR and C-13 CP MAS NMR were used to probe the mesoporous structure and the nature of chromium sites in the hybrid catalyst matrix. PXRD, TEM and N-2 adsorption-desorption analysis showed that the original hexagonal structure of the materials is maintained after chromium substitution, while FT-Raman, UV-Vis and XPS analysis showed that chromium atoms exist in a highly dispersed state. The catalytic performance of the chromium-containing hybrid samples was tested in the liquid-phase oxidation of cyclohexane with aqueous hydrogen peroxide (H2O2) and non-aqueous tert-butylhydroperoxide (TBHP) as oxidants. The hybrid materials exhibited better catalytic activities and were more stable than the conventional Cr-MCM-41 catalyst. The higher catalytic activity of the new chromium-containing molecular sieves is attributed to the improved hydrophobicity of the materials and to the complementary structural features that facilitates the accessibility of cyclohexane to the active framework chromium sites. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Cr-MCM-41; Cr-PMO; Cyclohexane; hybrid mesoporous materials; Oxidation